2022
DOI: 10.3897/asp.80.e86008
|View full text |Cite
|
Sign up to set email alerts
|

Revision of recluse spiders (Araneae: Sicariidae: Loxosceles) preserved in Dominican amber and a total-evidence phylogeny of Scytodoidea reveal the first fossil Drymusidae

Abstract: Recluse or violin spiders in the genus Loxosceles (Scytodoidea: Sicariidae) are a diverse group (~140 extant species) including medically important species and distributed mainly in the Americas, Africa, and the Mediterranean region. In addition, this genus includes three fossil species from Miocene Dominican amber. Here we revise the taxonomy of these fossil species by examining, imaging and re-describing their type specimens. We find that L. defecta Wunderlich, 1988 and L. deformis Wunderlich, 1988 are bona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Wood et al (2013) used tip-dating to show that Palpimanoidea diversification was shaped by the break-up of Pangaea in the Mesozoic. Recently, using morphology observed under microCT, Magalhaes et al (2022) discovered that the holotype of Loxosceles aculicaput Wunderlich, 2004 (Sicariidae) is actually a misidentified Drymusidae, which was the first fossil from the latter family and placed in a phylogeny. Fossils are also useful in reconstructing trait evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (2013) used tip-dating to show that Palpimanoidea diversification was shaped by the break-up of Pangaea in the Mesozoic. Recently, using morphology observed under microCT, Magalhaes et al (2022) discovered that the holotype of Loxosceles aculicaput Wunderlich, 2004 (Sicariidae) is actually a misidentified Drymusidae, which was the first fossil from the latter family and placed in a phylogeny. Fossils are also useful in reconstructing trait evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (2013) used tip-dating to show that Palpimanoidea diversification was shaped by the break-up of Pangaea in the Mesozoic. Recently, using morphology observed under microCT, Magalhaes et al (2022) discovered that the holotype of Loxosceles aculicaput Wunderlich, 2004 (Sicariidae) is actually a misidentified Drymusidae which was the first fossil from the latter family and placed in a phylogeny. Fossils morphology is also useful in reconstructing trait evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the family Drymusidae are popularly known as false violin spiders due to their external resemblance to the brown spiders (Labarque et al 2018), also known as violin or recluse spiders, which are species of medical importance of the genus Loxosceles Heineken & Lowe, 1832 (Sicariidae). Nonetheless, this resemblance is superficial since recent morphological and molecular studies have revealed that Drymusidae is closely related to the Australian family Periegopidae, both belonging to the Scytodoidea superfamily, which includes Sicariidae and other families (Labarque et al 2018;Magalhaes et al 2022). Drymusidae comprises two genera: the African Izithunzi Labarque, Pérez-González & Griswold, 2018 with five species and the Neotropical Drymusa Simon, 1892 with 12 species (Labarque et al 2018;World Spider Catalog 2023).…”
Section: Introductionmentioning
confidence: 99%